Promocão do letramento emergente de crianças com Síndrome de Down - Dias, Mirian Vieira Batista (Universidade Federal de São Carlos, 2016)
The literature highlights the importance of Emerging Literacy and the development of knowledge about writing and its functions acquired by children in the period of early childhood education for success in literacy. The research shows that, through contacts with actions of reading and writing conducted by adults, young children with typical development and non-typical develop: 1) interest in books; 2) interest in stories read by the adult; 3) active participation while reading; 4) knowledge about the book handling; 5) direction of reading; 6) concepts about writing conventions; 7) distinction between written and unwritten; 8) functions of writing; 9) recognition of global and common words in the environment; 10) recognition of the first name; 11) reading pretends; 12) tracing and evidence of the alphabetic foundation. The main objective of the study was to examine the development of knowledge, skills and attitudes of the emerging literacy of students with intellectual disabilities exposed to a contact experience with reading books and encouragement to participate in activities that stimulated the different components of emergent literacy. This study is characterized as a single subject design. Study participants were two students with intellectual disabilities and Down syndrome attending the resource room of a public school in ordinary school with kindergarten rooms. The activities were conducted individually by the proposer of the study. Participant 1 had the opportunity to participate in 15 sessions of weekly activities and Participant 2 in 11 stimulating sessions, of different components of emerging literacy. As a result of the program, the study participants were able to become familiar with the components of emergent literacy through shared reading, the autonomy to choose the books, hear a variety of stories with effective participation, and participation in activities that contributed to the understanding of conditions which appears necessary for the acquisition of emergent literacy components occurred during the sessions. The participants demonstrated a reduced evolution relative to the emerging literacy regarding the writing activities, which were not present in the repertoire of the participants at the beginning of the intervention.They identify conditions that may have contributed to the results that were not consistent with results obtained in similar studies.
Literacy promotion of children's emerging with down syndrome
Keywords: Educação especial; Letramento emergente; Educação infantil; Síndrome de Down; Special education; Emergent literacy; Child education; Down's Syndrome; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO